Mental wellbeing of drug addicts’ wives: roles of economic strain, marital conflict, and social support - Haikal Anuar Adnan; Zarinah Arshat; Rumaya Juhari; Nurul Saidatus Shaja’ah Ahmad Shahril (Penerbit Universiti Kebangsaan Malaysia, 2025)
Low-income wives of drug-addicted individuals face significant life challenges, including economic strain, marital conflict, and the responsibility of raising children alone. These stressors are linked to low mental wellbeing. This study aims to explore the relationships between economic strain, marital conflict, social support, and mental wellbeing in this population. A cross-sectional correlational study was conducted with 132 low-income wives of drug addicts in Malaysia. Participants completed one set of questionnaire contains the Economic Strain Scale (ESS), Braiker-Kelly Marital Conflict Scale (BKMCS), Multidimensional Scale of Perceived Social Support (MSPSS), and the Short Warwick-Edinburgh Mental Wellbeing Scale (SWEMWBS). Data analysis was performed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS version 4.0. The path analysis revealed direct relationships between economic strain and marital conflict, and between social support and mental wellbeing. However, there was no direct relationship between marital conflict and mental wellbeing or between marital conflict and social support. The findings suggest that economic strain contributes to marital conflict, while social support plays a key role in enhancing mental wellbeing. These results underline the importance of psychoeducational strategies for supporting wives of drug addicts, particularly in emphasizing the value of social support networks to improve their mental health. This study highlights the need for targeted support systems for spouses of individuals with substance abuse issues, aiming to improve their mental wellbeing through social connections and support.